Nouveaux modèles de négociation, de résolution de conflits et de solutions conjointes de problèmes : rapport général - Sexton, Jean (Relations industrielles / Industrial Relations, 1996)
English title: New models of negotiations, dispute resolution and joint problem solving. Abstract: Conflicts, tension and disputes are at the heart of industrial relations. At the end of the day, understanding, preventing and finding solutions to them constitute the essential subject matter of industrial relations. This is nothing new, but what is new are the efforts of imagination and experimentation being made just about everywhere in the world to find new, effective means to achieve the very purpose of industrial relations, that is, the resolution of disputes. An evaluation of the results of these new methods is presented.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z